(3GdeNJGQ ef HOGFY GdHOGFIs - (3CHh eMeO HOQ GdOjf GdMSf Hf YeQh Hf GdMSf Hf MHjH GdMdHjs; (3Ydj Hf XGaQ Hf MSjf GdCROj GdNRQLj, CHh GdMSf LeGd GdOjf,J (B613 (3g` s ((3eOjfI GdbSWfWjfjI s)
(3ChdgG (B:s
(3hHYO, agPg fhGOQ GNJQJgG ef cJGH HOGFY GdHOGjI hbO LYdg eDdag QMeg Gddg efMUQkG aj NeSI CHhGH s
(3BNQgG (B:s
(3CaMeJfj MSfkG hMb CjGOjc GdJj dG JYO HGdEMUGA gPG BNQ eG GNJGQg HOQGdOjf ef cJGH HOGFY GdHOGFI ddCOjH GdYdGeI Ydj Hf XGaQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B113s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B21 s
Keywords: (3GdCOHs